Assessment of normal myelination in infants and young children using the T1w/T2w mapping technique - Filimonova, Elena; Amelina, Evgenia; Sazonova, Aleksandra; Zaitsev, Boris; Rzaev, Jamil (Frontiers in Neuroscience, 2023)
Background: White matter myelination is a crucial process of CNS maturation. The purpose of the study was to validate the T1w/T2w mapping technique for brain myelination assessment in infants and young children. Methods: Ninety-four patients (0-23 months of age) without structural abnormalities on the brain MRI were evaluated using the T1w/T2w mapping method. The T1w/T2w signal intensity ratio, which reflects the white matter integrity and the degree of myelination, was calculated in various brain regions. We performed a Pearson correlation analysis, a LOESS regression analysis, and a 2nd order polynomial regression analysis to describe the relationships between the regional metrics and the age of the patients (in months). Results: T1w/T2w ratio values increased rapidly in the first 6-9 months of life, then slower thereafter. The T1w/T2w mapping technique emphasized the contrast between myelinated and less myelinated structures in all age groups, which resulted in better visualization. There were strong positive correlations between the T1w/T2w ratio values from the majority of white matter ROIs and the subjects' age (R=0.7-0.9, p < 0.001). Within all analyzed regions, there were nonlinear relationships between age and T1/T2 ratio values that varied by anatomical and functional location. Such regions as the splenium and the genu of the corpus callosum showed the highest R2 values, indicating less data scatter and a better fit to the model. Conclusion: The T1w/T2w mapping technique may enhance our diagnostic ability to assessment myelination patterns in infants and young children’s brain.